Pengembangan Kreativitas Berkelanjutan Melalui Pelatihan Pembuatan Sabun Ramah Lingkungan Dari Minyak Jelantah - Isni, Khoiriyah; Sabrina Salsabila Agustiningrum; Diany Fitiar Hapsari Putri; Imelda Editasari; Mupidah; Anindya Pramesty Sekar Amarilis; Zainal Abidin Daeng Matally; Ayu Saidah (Universitas Muhammadiyah Surakarta, 2024)
The waste problem is an urgent problem that needs to be addressed now in the Special Region of Yogykarta Province (DIY). The closure of the Piyungan Integrated Waste Disposal Site (TPST) is a strong appeal for the entire community to be able to process waste at the household level. Based on the results of the situation analysis and solutions related to the waste problem in RT 10 and RT 12 Jomblangan Hamlet, Banguntapan, Bantul, it was found that the community needs processing of used cooking oil waste. The aim of this community service activity is to develop sustainable creativity through training in making environmentally friendly soap from used cooking oil. The activity methods used were education, discussion and training which was carried out for two days with a duration of 120 minutes per day (13 and 15 June 2023) which was attended by 40 housewives. Evaluation of activities is carried out through pre-test and post-test questionnaires. The results of the activity statistically showed an increase in participants' knowledge regarding waste and processing used cooking oil waste into environmentally friendly soap from 83.5% to 93.25% (p=0.011). Household waste processing activities with creative ideas can be carried out regularly, so that they can contribute to efforts to reduce waste in the DIY area